Іmprovement of accounting and calculations for the payment of labor in agricultural enterprises based on a systematic approach and organizational innovations - Svitlana Skrypnyk; Svitlana Koval; Inesa Shepel (Економічний вісник університету, 2022)
The subject of the study is the theoretical and practical aspects of improving accounting and payroll calculations. The purpose of the article is to identify problems and justify directions for improving the accounting of wages and salaries in agricultural enterprises on the basis of a systematic approach and the implementation of organizational innovations. The methodological basis of the article was the theoretical and methodological provisions of accounting and taxation; normative-legislative acts and fundamental works of scientists on this issue. The following methods were used: historical, abstract-logical, dialectical, monographic, system-structural analysis and synthesis, statistical-economic, double-entry, accounting accounts, balance sheet, accounting and financial reporting. Results of the article. Based on the principles of the system approach, the difference between remuneration as a process and wages as a result of labor, as well as their identical features, was revealed. The latter allow to develop and identify the forms of labor payment, their content and advantages and possibilities of application. The trend of increasing individualization of labor and its payment on the basis of contracts has been determined. The importance of accounting for labor remuneration for increasing its productivity and ensuring the efficiency of agricultural enterprises is substantiated. Field of application of results. The received practical recommendations and developments can be implemented in the economic and accounting activities of enterprises; divisions of tax services; educational and research process of economic and accounting faculties of higher education institutions. Conclusions. A systematic approach to labor and its accounting made it possible to determine the difference between wages and wages; characterize tariff and other forms of their implementation as organizational innovations; justify accounting tasks. Completion of payroll accounting tasks has a positive effect on the image, functioning efficiency and competitiveness of the development of agrarian enterprises through the stimulation of compliance with the rules of internal labor regulations, the conscientious performance of their duties by employees, and a favorable moral climate in the team. This ensures the coherence of the accounting work from the moment of filling out the primary document to the display of information about accrued and paid wages in the reporting. It is the correct organization of remuneration, observance of fair proportions, ratios, accounting of wage amounts with conditions and results of work that serve as a primary factor in stimulating labor productivity, employee interest in improving results and quality of work.